The fertility-sparing treatment and outcome of epithelioid trophoblastic tumor isolated to lung: a case report and review literature - Huang, Zengshu; Yu, Yingjuan; Wen, Darong; Wang, Nan; Zeng, Liping (Frontiers in Oncology, 2024)
Background Epithelioid trophoblastic tumor (ETT) is the rarest gestational trophoblastic tumor, with poor response to chemotherapy. Hysterectomy, as the cornerstone therapy for early ETT, is particularly challenging in reproductive-age women who often have a strong desire for fertility preservation. The management of extra-uterine ETT could be even more complicated and inconsistent. Here we reported a case of isolated ETT lesions in lungs managed with thoracic surgery without hysterectomy. Case presentation A 32-year-old woman presented with amenorrhea for 2 months. Her serum β- human chorionic gonadotropin (hCG) levels fluctuated between 52 and 75 mIU/mL. The patient underwent removal of intrauterine device and suction and curettage, but only proliferative endometrium was found. Methotrexate was given for a provisional diagnosis of ectopic pregnancy of unknown location, while β-hCG had no significant decline. She complained of mild chest pain during the past half year, and the chest computed tomography (CT) result showed two mixed ground-glass nodules of 24 mm × 14.2 mm in right upper lobe and 10 mm × 8 mm in the right lower lobe and a thin-walled cavity in the posterior segment of the left lower lobe. Right upper wedge resection and right lower segmentectomy were performed 3 months later. The result of the pathological examination of pulmonary mass indicated an epithelioid trophoblastic tumor. She was diagnosed with ETT at stage III (with right lung metastasis) according to FIGO 2000. Her menstrual cycle recovered within 1 month after the first thoracic surgery. However, β-hCG was elevated again to 9 mIU/mL, and the positron emission tomography/computed tomography (PET/CT) scans revealed the consolidation of the nodule in the left lower lobe which enlarged to about 1.0 cm × 1.7 cm. Her second pulmonary surgery without hysterectomy was conducted. Followed for 12 months for postoperative monitoring, the patient was found to be disease-free with negative results of serial serum β-hCG and chest CT. Conclusion Our case highlights the efficacy of fertility-sparing surgery for isolated ETT in lungs. The surgical management of pulmonary isolated ETT could be individualized under long-term supervision. Sporadic reports on the favorable outcome of extra-uterine ETT with fertility-sparing surgery were described in the last decades. The safety of this surgical strategy might be warranted only if enough reliable data is accumulated.